A comparison between the ICNP and the ICF for expressing nursing content in the electronic health record. (October 2021) - Florin, Jan; Strandberg, Elisabeth; Jansson, Inger; Ehrenberg, Anna; Björvell, Catrin
Abstract: Background: The use of standardised terminologies for electronic health records (EHRs) is important and a sufficient coverage of all aspects of health care is increasingly being developed worldwide. The International Classification of Functioning, Disabilities and Health (ICF) is suggested as a unifying terminology suitable in a multi-professional EHR, but the level of representation of nursing content is unclear. Objectives: The aim was to describe lexical and semantic accordance in relation to comprehensiveness and granularity of concepts between the International Classification of Nursing Practise (ICNP) and the ICF. Methods: 806 pre-coordinated concepts for diagnoses and outcomes in the ICNP terminology were manually mapped to 1516 concepts on level 4–6 in the ICF. Results: Several dimensions of nursing diagnoses and outcomes in the ICNP were missing in the ICF. 60% of the concepts for diagnosis and outcome in the ICNP could not be stated using the ICF while another 31% could only be matched either as a subordinate or as a superordinate concept. Conclusions: The lexical and semantic accordance in relation to comprehensiveness and granularity between concepts in the ICNP and ICF was rather low. A large proportion of concepts for diagnoses and outcomes in the ICNP could not be satisfactorily stated using the ICF. Standardised terminologies rooted in a nursing tradition (e.g., the ICNP) is needed for communication and documentation in health care to represent the patient's health situation as well as professional diagnostic decisions and evaluations in nursing.